Penguatan Karakter Holistik Anak Marginal di Kecamatan Kedungkandang Melalui Mission-Based Learning Berbasis Eco-Guardians Guna Menyongsong Generasi Emas 2045 - Ramadhan, Dede; Hipi, Tiara Wahyuni Rahmawati; Irfansyah, Mohamad Lutfi; Putri, Zhelyta Aulia Andriani; Rahmastya Putri, Wanda; Wahyuni, Lilik (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Malang City, like many cities in Indonesia, faces complex challenges, especially in access to education, health, and economic opportunities. This research examines strengthening the holistic character of marginalised children in Kedungkandang Sub-district through the Eco-Guardians-based Mission-Based Learning method. This method aims to shape holistic character including emotional, social, and environmental dimensions to create a competitive and environmentally sound young generation. A descriptive qualitative approach was used with data from the non-formal education institution Laskar Belajar, marginalised children, and Brawijaya University creativity programme students, collected through observation, in-depth interviews, questionnaires, and Focus Group Discussions (FGDs). The results showed that the collaboration between students and marginalised children effectively increased engagement and motivation through a mission that focused on character development and environmental awareness. The implementation of this programme improved the quality of character, environmental awareness, and waste management skills of marginalised children. Holistic character education is important to address social and environmental challenges in Kedungkandang. The Eco-Guardians programme offers a comprehensive solution that not only develops character but also improves the economic welfare and environmental awareness of marginalised children. The programme is expected to become a sustainable model of holistic character education to support the achievement of the Golden Generation 2045.